Disorders of acid-base balance promote rumen lipopolysaccharide biosynthesis in dairy cows by modulating the microbiome - Hou, Guobin; You, Jingtao; Zhuang, Yimin; Gao, Duo; Xu, Yiming; Jiang, Wen; Li, Sumin; Zhao, Xinjie; Chen, Tianyu; Zhang, Siyuan; Liu, Shuai; Wang, Wei; et al. (Frontiers in Microbiology, 2024)
IntroductionDisorders of acid-base balance in the rumen of dairy cows have a significant impact on their health and performance. However, the effect of transient differences in pH on susceptibility to subacute ruminal acidosis (SARA) and lipopolysaccharide (LPS) biosynthesis in dairy cows remains unclear.MethodsIn this study, milk, serum, and rumen fluid samples from 40 Holstein dairy cows (on d 56 postpartum) with different rumen pH (2–4 h after morning feeding) were explored to investigate the difference of susceptibility to SARA and the correlation between microbiome, LPS and inflammation. These cows were categorized into low pH (LPH, pH ≤ 6.0, n = 20) and high pH (HPH, pH ≥ 6.5, n = 20) groups.ResultsThe results showed that LPH group increased the concentrations of total volatile fatty acids, acetate, propionate, butyrate and valerate. However, milk yield and milk compositions were unaffected. Compared to the HPH group, the LPH group increased the concentrations of serum BHBA, NEFA, LPS, HIS, IL-2, IL-6, TNF-α, and MDA, and decreased the concentrations of serum IgA, IgM, IgG, SOD, T-AOC, and mTOR. In addition, the LPH group decreased the copies of Ruminococcus flavefaciens and increased the copies of Fibrobacter succinogenes. Microbial community analysis isupplendicated a significant difference in bacterial composition between the two groups. At the phylum level, Bacteroidota and Firmicutes were enriched in the LPH and HPH groups, respectively. At the genus level, the dominant bacteria in the LPH group were Prevotella. Additionally, the LPH group increased the proportions of Gram-negative phenotypes, potentially pathogenic phenotypes and LPS biosynthesis. The close correlation between two key enzymes for LPS synthesis LpxL and LpxM with rumen pH, inflammatory markers, and microorganisms indicates that low pH may increase the risk of inflammation by facilitating the lysis of Gram-negative bacteria and the release of penta-acylated LPS. Penta-acylated and hexa-acylated LPS may be mainly derived from Prevotella and Succinivibrionaceae_UCG-001, respectively.DiscussionOverall, these results support the notion that transient low pH could reflect the risk of cows suffering from SARA and associated inflammation and is strongly associated with penta-acylated LPS. Our findings provide new insights into ruminant health improvement and disease prevention strategies.